Screening For Herbicidal And Growth Promotor Activities In Marine Bacteria - PREM ANAND,T.,; C. FELICIA SHANTHINI; C. CHELLARAM (International Journal of Pharma and Bio Sciences, 2012)
Herbicides for practical use today are mostly synthetic compounds and they may be classified as follows on the basis of their mode of action, herbicides inhibiting photosynthetic electron transfer, herbicides affecting plant hormonal actions, herbicides interfering with nutritive metabolism, herbicides affecting cell division and microherbicides. Sooner or later weeds acquire resistance to the existing herbicide and thus the continued development of new and potent drugs for controlling them is required. This development of new herbicides must always take into consideration the problem of environmental pollution. Work regarding herbicidal activity relating to marine natural products is very limited. Screening for herbicidal activity was carried out using 250 marine bacterial strains by Lemna assay. Herbicidal activity was noted in 50 strains, out of which eight strains exhibited90% inhibition at a very low concentration of 5 ppm. Dwarfing and bleaching offronds were noticed as effects of various crude extracts. In the course of this study growth promoter activity was also noted in 75 strains.